Differences in the severity of indicators characterising the subjective assessment of lifestyle and somatic health of women aged 36-40 and 41-45 years - Ruban , L. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. The subjective assessment of the quality of life and somatic health of women in the second period of adulthood is multicomponent and depends on a number of factors. Women aged 36-45 years are usually aware of changes in their bodies, but do not always have the desire, resources or motivation to make lifestyle changes. Women in the second period of adulthood experience the first occurrence of chronic diseases, and a decrease in physical activity contributes to the deterioration of somatic health. The purpose of the study is to analyse the questionnaire and assess the degree of subjective assessment of quality of life and somatic health in order to further determine the differences in the indicators of women in the group of 36-40 years and the group of 41-45 years. Research methods: we studied 79 women. Women were divided into two groups: group 35-39 years old – 36 women, group 40-46 years old – 43 women. We conducted a questionnaire based on the test ‘Subjective assessment of lifestyle and somatic health’, which consists of 10 questions. The test questions relate to attitudes towards stressful situations, diseases, body weight, sleep, nutrition, alcohol and tobacco consumption, physical education and the use of health improvement methods in everyday life. Results. Comparison of the subjective assessment of lifestyle and somatic health of women in the two age groups shows that the decline in their final score with age was not natural. significant differences between women aged 36-40 and 41-45 years are a markedly reduced level of physical activity, ability to manage stress and satisfaction with their own weight, and more frequent health problems in older women. Sleep and eating habits were similar. The frequency of alcohol consumption was higher in women aged 36-40. In women aged 36-40, the median total score was 39 points, while in the older group of 41-45, this figure dropped to 36 points, i.e. by 3 points. The difference was statistically insignificant (p>0.05), and such data do not confirm the previous information that women aged 41-45 years led a more unsatisfactory lifestyle and had a worse state of somatic health. Conclusions. Women aged 36-40 years are more likely to lead a more active lifestyle, but do not always take care of regular rest and health. Women aged 41-45 have a greater awareness of health and disease prevention, but agerelated changes and complaints of chronic fatigue are already noticeable. With age, interest in maintaining quality of life increases.